2007
DOI: 10.1097/sla.0b013e318148566
|View full text |Cite
|
Sign up to set email alerts
|

Hormonally Active Women Tolerate Shock-Trauma Better Than Do Men

Abstract: Objective: To test the hypothesis that comparably injured women, especially those in the hormonally active age groups, would manifest a better preserved hemodynamic response and tissue perfusion after major trauma than do men. Summary Background Data: The notion that premenopausal women are more resistant than men to shock and trauma has been shown in numerous preclinical models. However, human studies on the effects of gender on outcome after shock-trauma are less clear, and none has examined the effect of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 44 publications
2
103
2
9
Order By: Relevance
“…Correlations between CRP, Crea, sodium, and ISS might be stress induced as a direct consequence of the injury or a consequence of inner organ impairment. The fact that we could not detect a gender-related difference, when it comes to overall survival, is in contrast to the finding of Deitch et al [5] in a study with more than 4,000 patients, stating that hormonally active women have a better physiological response to similar degrees of shock and trauma than their male counterparts.…”
Section: Discussioncontrasting
confidence: 85%
“…Correlations between CRP, Crea, sodium, and ISS might be stress induced as a direct consequence of the injury or a consequence of inner organ impairment. The fact that we could not detect a gender-related difference, when it comes to overall survival, is in contrast to the finding of Deitch et al [5] in a study with more than 4,000 patients, stating that hormonally active women have a better physiological response to similar degrees of shock and trauma than their male counterparts.…”
Section: Discussioncontrasting
confidence: 85%
“…30 Some studies have investigated hormonally active differences in patients with posttraumatic shock but have not focused on brain injury. 32 The present study found that, compared with males of a similar age, premenopausal females in Hong Kong had a higher chance of having brain edema. The findings are supported by those of other researchers 35 who concluded that females showed significantly higher frequencies of brain edema and intracranial hypertension compared with males, and the highest rates were found in female patients younger than 51 years.…”
Section: Commentmentioning
confidence: 81%
“…Clinical data are modestly supporting (e.g., Deitch et al 11 and Gannon et al 27 ) or nonsupporting (e.g., Magnotti et al 28 and Schoeneberg et al 29 ). The nonsupporting studies may be the ones in which the hormonal status of the subjects at the time of trauma was unknown.…”
Section: Discussionmentioning
confidence: 96%